Blockchain dan Asuransi Mikro: Kajian Literatur tentang Peluang dan Tantangan Inovasi - Bani, Pristiwanto (P3M Trisakti School of Insurance (TSI), 2024)
Microinsurance has emerged as an important solution in risk management for low-income communities, especially in developing countries. On the other hand, blockchain technology offers promising innovations with the ability to improve transparency, efficiency, and security in various sectors, including insurance. This literature review explores the opportunities and challenges of innovation in the integration of blockchain technology with microinsurance. Using a narrative literature review method, we analysed relevant scientific articles from various academic databases such as Scopus, Web of Science, Google Scholar and other trusted sources to provide a comprehensive overview of this topic. Key findings indicate that blockchain offers significant potential to improve the efficiency, transparency, and accessibility of microinsurance, especially in developing countries. This article examines the potential integration between microinsurance and blockchain technology, as well as the challenges faced in its implementation, we find that the combination of these two fields can create an ecosystem that is more inclusive and responsive to the needs of the community. However, challenges such as regulatory issues, infrastructure limitations, and the need for digital literacy still need to be overcome. The review also identifies several key areas for further research, including the development of sustainable business models, increasing interoperability between blockchain systems and traditional insurance, and exploring the socio-economic implications of widespread adoption of this technology. Overall, blockchain integration in microinsurance shows transformative potential to enhance financial inclusion, although its implementation requires a careful and collaborative approach from various stakeholders.